Analisis Pengaruh Pengangguran Terhadap Kemiskinan di Kabupaten Rembang Menggunakan Metode Regresi Linear - Ika Nurul Hidayati; Eriska Fitri Kurniawati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to examine the impact of the unemployment rate on poverty levels in Rembang Regency by applying the linear regression method. The data used in this study are secondary data in the form of time series data covering the period from 2005 to 2025, obtained from the Central Bureau of Statistics (BPS) of Rembang Regency. The analytical method employed is simple linear regression using the Ordinary Least Squares (OLS) approach to understand the relationship and the magnitude of the effect of the independent variable (unemployment) on the dependent variable (poverty). The results of the study indicate that there is a positive relationship between the number of unemployed people and the poverty level. This is reflected in the regression coefficient value of 7,294, which means that every one-unit increase in unemployment will lead to an increase in poverty by 7,294 units, assuming all other variables remain constant. Furthermore, the results of the t-test analysis show that the unemployment rate has a significant effect on poverty, with a significance value of 0.001, which is lower than 0.05. Therefore, it can be concluded that the unemployment rate has a significant impact on the increase in poverty levels in Rembang Regency. Thus, the government needs to implement policy measures oriented toward job creation and improving the quality of human resources in order to reduce unemployment and poverty rates sustainably.